###### Recent Posts

I'm busy working on my blog posts. Watch this space!

###### Featured Posts

*If g(x)= -4x^2-3x+2, determine g(-2)?*

*If g(x)= -4x^2-3x+2, determine g(-2)?*

September 15, 2019

If g(x)= -4x^2-3x+2, determine g(-2)?

Algebra 1, August 2019 Regent exam

Answer and Explanation:

We have a function g of x, where x can be any number or variable. To calculate g(-2), all we need to do is to plug in -2 in the equation everywhere we see x.

Therefore, this equation becomes g(-2)= -4(-2)^2-3(-2)+2 = -4(4)+6+2= -8

The answer for this problem is -8

Hint: Every time we have a function such as g(x) and are asked to calculate g of something, we just plug that something instead of x.

Let's take a look at a couple of other examples.

Lets say we have f(x) = 3x-5

Let's now calculate f(3), f(2a) and f(3b-4)

Again, we need to keep in mind wherever we see x, just plug in the new value we see in parenthesis for the function.

f(3) = 3(3)-5 = 4

f(2a) = 3(2a)-5 = 6a-5

f(3b-4) = 3(3b-4) -5 = 9b-12-5= 9b-17

At Transformation Tutoring we have incredible Math Tutors who are passionate about education and helping students achieve their dreams. We work in Brooklyn, Queens, Manhattan and online.

For inquiries please call 646-407-9078. Our math tutors specialize in: Geometry, Calculus I, II and III, Linear Algebra, Algebra, Trigonometry, Probability and many more.